Air pollution: an analysis of state intervention - Ribeiro, Sandra (2020)
The world has undergone many changes in recent decades, changes mainly derived from globalization, which takes business management and even the governance of the country to another level. Globalization and the growing development felt worldwide lead to the economic and social development of states, increasingly concerned and focused on the good environmental practices of an economy. The main objective of this study is to present how the state became the main actor in the treatment of air pollution. To this end, firstly, the field of public economy is briefly characterized and historically contextualized, followed by what constitutes a market failure and common methods of correcting it. There is an emphasis on negative externalities, as this fits in with the central theme of the work. We delve into the case of air pollution by presenting the reason why it is considered an economic problem, analysing how environmental policies can affect GDP and presenting what has been done to combat this problem, both in the European Union and in Portugal